(untitled) (mathematica didactica, 2009)
The productive use of mistakes is an important element for the development of mathematical competency. Against the background of the dominant teaching script in German classrooms, are there possibilities of improving the way how teachers deal with mistakes in their classrooms and which impacts can be expected from corresponding teacher training activities? As part of the evaluation research of a video-based in-service teacher training, this study examines developments of professional knowledge about dealing with mistakes. Quantitative and qualitative findings suggest short-term and long-term changes of professional knowledge in this domain.